Liver Disease Associated with Inflammatory Bowel Disease - Kurniawan, Juferdy; Budiman, Refael Alfa (The Indonesian Society for Digestive Endoscopy, 2024)
Inflammatory Bowel Disease (IBD) is a chronic condition characterized by persistent inflammation of the gastrointestinal tract, comprising ulcerative colitis (UC) and Crohn’s disease (CD). While the current global incidence of IBD exceeds 0.3% in Western nations, Indonesia reports a comparatively lower prevalence however with projections indicate a potential rise in incidence from 2020 to 2050. Hepatobiliary manifestation is one of the most common extraintestinal manifestations of IBD. Some of the liver disease associated with IBD had similar background immune response, inflammatory reaction, similar risk factor, or due to the treatment of IBD. Primary sclerosing cholangitis (PSC) has close association with IBD and both affect the prognostic and disease progression of each other. Non-alcoholic fatty liver disease (NAFLD) shares common metabolic risk factors. Several drugs used as the treatment of IBD might cause hepatic injury especially due to the long treatment duration of IBD. Hepatitis B reactivation is another concerning event found after prolonged used of immunosuppressive drugs of IBD. Therefore, close monitoring of liver function test periodically is a mandatory test to screen liver disease in IBD patients. Keyword: Inflammatory bowel disease, liver disease, autoimmune hepatitis, drug-induced liver injury